An SAR study of hydroxy-trifluoromethylpyrazolines as inhibitors of Orai1-mediated store operated Ca2+ entry in MDA-MB-231 breast cancer cells using a convenient Fluorescence Imaging Plate Reader assay. Issue 12 (23rd July 2018) - Stevenson, Ralph J.; Azimi, Iman; Flanagan, Jack U.; Inserra, Marco; Vetter, Irina; Monteith, Gregory R.; Denny, William A.
Graphical abstract: Abstract: The proteins Orai1 and STIM1 control store-operated Ca 2+ entry (SOCE) into cells. SOCE is important for migration, invasion and metastasis of MDA-MB-231 human triple negative breast cancer (TNBC) cells and has been proposed as a target for cancer drug discovery. Two hit compounds from a medium throughput screen, displayed encouraging inhibition of SOCE in MDA-MB-231 cells, as measured by a Fluorescence Imaging Plate Reader (FLIPR) Ca 2+ assay. Following NMR spectroscopic analysis of these hits and reassignment of their structures as 5-hydroxy-5-trifluoromethylpyrazolines, a series of analogues was prepared via thermal condensation reactions between substituted acylhydrazones and trifluoromethyl 1, 3-dicarbonyl arenes. Structure-activity relationship (SAR) studies showed that small lipophilic substituents at the 2- and 3-positions of the RHS and 2-, 3- and 4-postions of the LHS terminal benzene rings improved activity, resulting in a novel class of potent and selective inhibitors of SOCE.